Modulation of Staphylococcus aureus Biofilm Formation through Subinhibitory Concentrations of Biogenic Silver Nanoparticles and Simvastatin - Ana Carolina Furian da Silva; Sindy Magri Roque; Marta Cristina Teixeira Duarte; Gerson Nakazato; Nelson Durán; Karina Cogo-Müller (MDPI AG, 2024)
Staphylococcus aureus is a causative agent of nosocomial infections and its antibiotic-resistant strains give cause for concern. Solutions are being explored to improve treatment for these infections, including repositioning drugs such as statins and using nanoparticles with antimicrobial properties. This study evaluated the antimicrobial effects of simvastatin (SIM) and biologically synthesized silver nanoparticles (bio-AgNPs) in isolate form and in combination using assays of minimum inhibitory concentration (MIC), an in vitro biofilm model, and the association of antimicrobials against clinical strains of S. aureus. Bio-AgNPs showed a 53.8 ± 1.23 nm mean diameter and standard deviation, a 0.23 polydispersity index, and a −25.66 ± 2.19 mV mean potential and standard deviation. Transmission electron microscopy confirmed the formation of nanoparticles, and the presence of Ag0 and AgCl. S. aureus strains were sensitive to bio-AgNPs and SIM, showing 31.88-187.5 and 74.66-149.32 μM concentrations, respectively. The association assay showed 2.0 fractional inhibitory concentration indices (i.e., indifferent for clinical strains) and 0.32 values for the standard ATCC 29213 strain (synergy). Biofilm inhibition assays with isolated SIM and bio-AgNPs showed decreased biofilm formation 4× to ⅛ MICs concentrations, showing no synergism in association. These findings evince that simvastatin and bio-AgNPs at subinhibitory concentrations can serve as antimicrobial agents against S. aureus biofilm.